2016
DOI: 10.1007/s11356-016-7156-5
|View full text |Cite
|
Sign up to set email alerts
|

Disodium N,N-bis-(dithiocarboxy)ethanediamine: synthesis, performance, and mechanism of action toward trace ethylenediaminetetraacetic acid copper (II)

Abstract: A new effective multi-dithiocarbamate heavy metal precipitant, disodium N,N-bis-(dithiocarboxy) ethanediamine (BDE), was synthesized by mixing ethanediamine with carbon disulfide under alkaline conditions, and it was utilized for removing trace ethylenediaminetetraacetic acid copper (II) (EDTA-Cu) from wastewater. Its structure was confirmed by ultraviolet spectra, Fourier transform infrared spectra, scanning electron microscopy, thermogravimetric analysis, and elemental analysis. The removal performance of ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As shown in Figure f, oligo-DTC prepared with NH 3 /DCE ratios of 3:1–5:1 presented typical UV–vis spectra of DTCs, with peaks at approximately 250 and 280 nm. , In contrast, oligo-DTC prepared with an NH 3 /DCE ratio of 1.5:1 or 2:1 exhibited relatively weaker oligo-DTC-related peaks, but there appeared by-product-related peaks at ∼330 and ∼230 nm. The UV–vis spectra of amination products (Figure S2) suggested that oligoamine obtained with NH 3 /DCE ratios of 3:1–5:1 was of higher purity, while oligoamine obtained with an NH 3 /DCE ratio of 1.5:1 or 2:1 contained undesired impurities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure f, oligo-DTC prepared with NH 3 /DCE ratios of 3:1–5:1 presented typical UV–vis spectra of DTCs, with peaks at approximately 250 and 280 nm. , In contrast, oligo-DTC prepared with an NH 3 /DCE ratio of 1.5:1 or 2:1 exhibited relatively weaker oligo-DTC-related peaks, but there appeared by-product-related peaks at ∼330 and ∼230 nm. The UV–vis spectra of amination products (Figure S2) suggested that oligoamine obtained with NH 3 /DCE ratios of 3:1–5:1 was of higher purity, while oligoamine obtained with an NH 3 /DCE ratio of 1.5:1 or 2:1 contained undesired impurities.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5a showed that oligo-DTC could effectively remove Ni ions in various complexed forms. Figure 5b,c compared the performance of oligo-DTC with that of similar DTCs derived from ethyleneimine-based amines, including PEI−DTCs, 16,42 EDA−DTC, 26 and PIP−DTC. 43 Oligo-DTC was highly effective for Ni removal at both pH 2 and pH S11 and S12), in agreement with the results reported in the literature.…”
Section: Removal Of Hms By Oligo-dtc and Similar Dtcsmentioning
confidence: 99%
See 1 more Smart Citation